A review of the genus Pachymerium C. L. Koch, 1847 (Geophilomorpha: Geophilidae) from Romania - Popovici, George (Zootaxa, 2024)
Based on the review of the original descriptions of Pachymerium antipai Căpușe, 1968, P. atticum Verhoeff, 1901 and P. tabacarui Căpușe, 1968 from Romania and the direct study of the external anatomy of P. ferrugineum (C. L. Koch, 1835) and Geophilus flavus (De Geer, 1778) from Romania, Egypt, Italy and Russia, P. antipai and P. aticum sensu Căpușe (1968) are proposed as junior subjective synonyms of P. ferrugineum, while P. tabacarui is proposed as a junior subjective synonym of G. flavus. The presence of P. atticum in Romania is hereby considered doubtful. Revisions to the diagnosis of Pachymerium are proposed to help differentiate it from other geophilid genera. A discussion of the relative suitability of different morphological characters for distinguishing species within Pachymerium is also included.